The Influence of Social Media on Visual Communication Learners - Shanthi, P; Bharathy, Thulasi Bharathy M (International Journal of Computer Sciences and Engineering, 2025)
The aim of this research is to study the social media's influence among the learners. Also, it investigates the influences of social media in the current educational scenario. The opinion of adult learners between the age groups of 19 to 21 is gathered through well-constructed questionnaire to study the influence of social media on the B.Sc visual communication learners. An opinion survey was also conducted among the B.Sc visual communication learners to study the influence of social media such as WhatsApp, Twitter and Facebook. Adult learners' have self-reliance, maturity, independent thinking capability, and decision-making ability. Even though many research works support the social media's influence among the adult learners, social media usage affects their exam performance. Furthermore, this research reveals the negative side of social media messages. The adult learners believe the social media messages without any verification. Social media use is very common among the tech-savvy new generation learners. It helps to form the social media groups in the educational set-ups. Also, it helps to communicate the information in group project works, continuous assessment works and internships. There is a link that exists between the high-level exam performance and the usage of social media. There is a link that exists between the social media message usages' duration and exam performance. The social media usage between 4 to 6 hours per day reduces the exam performance. The over usage creates a stress during the learning period. The social media usage between one and less than one hour per day develops the exam performance